Metric Space of Subcopulas: Jumpol Rachasingho, Santi Tasena - Team, Support (Thai Journal of Mathematics, 2018)
Sklar's theorem states that any joint distribution function can be written as a composition of its marginal distributions and a subcopula. Structural study of the latter is therefore natural. In this work, we dene a new metric on the spa